First trimester blood indices: a predictor of early and late onset preeclampsia - Meera; Patil, Ambika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preeclampsia is a condition that falls under the hypertension spectrum and is more common in pregnant women who are 20 weeks or older. It causes complications in 2% to 8% of pregnancies. This study sought to identify haematological preeclampsia markers in pregnant women who received prenatal care at tertiary care centre at Vijayapur, Karnataka, India. Methods: This was a case-control study conducted at a tertiary care centre in Vijayapura Karnataka, from 01 December 2023 to 31 May 2024. A total of 75 preeclamptic patients with early (<34 weeks of gestation) and late presentation (≥34 weeks of gestation) were selected as cases and equal number of normotensive pregnant females were taken as controls. All the cases and controls were analysed for blood indices. The means of continuous variables were compared with two tailed students t-test by using SPSS version 26.0 statistical software. Results: In the present study, we observed that 75 patients with diagnosed cases of preeclampsia, among them, 42.1% were early onset preeclampsia and 56.6% were late onset. After comparing means of blood indices between early and late onset of preeclampsia showed, WBC (early- 17.92±0.98; late- 16.08±0.78), neutrophils (early- 77.52±1.22; late- 75.97±0.47), lymphocytes (early- 26.33±.2.78; late- 31.01±2.62), platelets (early- 128.59±2.22; late- 131.93±3.62), NLR (early- 2.97±0.28; late- 2.46±0.19), PLR (early- 4.93±0.46; late- 4.28±0.34) and the statistical significant difference (p<0.05) seen in these parameters. Blood indices of cases and controls were as follows, hemoglobin (cases-10.45±1.31; controls- 10.89±0.53), MCV (cases- 87.67±1.39; controls- 85.14±2.82), RDW (cases- 13.09±78; controls- 13.80±0.0), WBC (cases- 16.87±1.6; controls- 15.58±1.22), eosinophils (cases- 4.49±0.79; controls- 4.08±0.47), lymphocytes (cases- 29.01±3.54; controls- 22.73±0.86), platelets (cases- 130.16±3.50; controls- 132.16±3.98), NLR (cases- 2.68±0.34; controls- 3.65±4.09), PLR (cases- 4.55±0.51; controls- 5.82±0.24). There was a significant difference (p<0.05) between cases and controls in above parameters. According to these results, blood indices of preeclampsia with early and late onset differed significantly from healthy controls. Conclusions: According to the study’s findings, elevated first-trimester RDW, WBC, neutrophils, lymphocytes, platelets, and NLR/PLR ratios may serve as clinically valuable indicators for preeclampsia prediction. Changes in several indicators point to a possible major role for inflammation in the pathophysiology of preeclampsia.